Securing a future for humanity and the planet in times of “AI” - Kirchschläger, Peter G. (Bogoslovni vestnik, 2025)
In 2024, the UN General Assembly has adopted a resolution aiming for “safe, secure and trustworthy artificial intelligence systems” and the “Pact for the Future” including a “Global Digital Compact” and a “Declaration on Future Generations”. It is now urgent to implement and build on the UN General Assembly resolution and the “Pact for the Future”. This article suggests that an International Data-BasedSystems Agency (IDA) needs to be established urgently at the UN as a global plat-form for technical cooperation in the field of data-based systems (DS) fostering human rights, safety, security, a rules-based international order, sustainability, and peaceful uses of data-based systems (DS) with a multilateral approach, as well as a global supervisory and monitoring institution and regulatory authority in the area of data-based systems (DS) responsible for access to market approval.
Keywords: artificial intelligence (AI); človekove pravice; Data-Based Systems (DS); ethics; etika; human rights; human Rights-Based Data-Based Systems (HRBDS); International Data-Based Systems Agency (IDA); Mednarodna agencija za podatkovne sisteme (MAPS); odgovornost; OZN; podatkovni sistemi; podatkovni sistemi (PS); responsibility; sustainability; temelječi na človekovih pravicah (PSČP); trajnost; umetna inteligenca (UI); UN